Studi Historis dan Analisis Arsitektur Masjid Jamik Silalas Sei Deli, Kecamatan Medan Barat - Batubara, Muhammad Aziz; Asari, Hasan; Faishal, Muhammad (Warisan: Journal of History and Cultural Heritage, 2023)
The integration of Islamic and cultural values, as well as local values in the Medan Barat Subdistrict, is marked by the emergence of new architectural representations in mosque design within the sacred realm of religious activities. This article examines the historical trajectory and architectural development of Jamik Silalas Sei Deli Mosque in the Medan Barat Subdistrict, encompassing its historical establishment, construction, and changes in the orientation of Islamic architectural styles over time. This study falls under the purview of Islamic architectural history and is a qualitative research endeavor employing historical research methods, including source collection, source criticism, interpretation, and historiography, with a specific focus on the Islamic architectural arts. The study reveals that the evolution of Islamic architecture at Jamik Silalas Sei Deli Mosque is influenced by the changing eras and local values in determining the mosque's development model. Furthermore, from a sociological perspective, the values embodied in this architectural art serve as a representation of the social and religious climate, which tends to be integrative within the community.